IMPROVEMENT OF METHODS EVALUATING THE EFFECTIVENESS OF THE CARS BRAKES - Pshinko, O. M.; Myamlin, S. V.; Prykhodko, V. I.; Shkabrov, O. A.; Stierinzat, Ya. M.; Ihnatov, H. S.; Korobka, B. O. (Science and Transport Progress, 2005)
In work the specified methods of an estimation of efficiency of brake system of cars are offered. These methods take into account variety of factors and as much as possible approach a settlement estimation of brake system to a real design.